2011
DOI: 10.1016/j.jcin.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The STAT-MI (ST-Segment Analysis Using Wireless Technology in Acute Myocardial Infarction) Trial Improves Outcomes

Abstract: A fully automated, field-based, wireless network that transmits ECGs automatically to offsite cardiologists for the early evaluation and triage of patients with STEMI shortens D2B times, reduces infarct size, limits ejection fraction reduction, and shortens LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 22 publications
4
49
1
4
Order By: Relevance
“…[26][27][28] However, in the United States, this group typically constitutes a small fraction of the total STEMI population in each network. 15,29 For the majority of STEMI patients, our data suggest that continued emphasis on the triage and diagnostic period in the ED is paramount to establishing consistently lower time to reperfusion therapy.…”
Section: Discussionmentioning
confidence: 83%
“…[26][27][28] However, in the United States, this group typically constitutes a small fraction of the total STEMI population in each network. 15,29 For the majority of STEMI patients, our data suggest that continued emphasis on the triage and diagnostic period in the ED is paramount to establishing consistently lower time to reperfusion therapy.…”
Section: Discussionmentioning
confidence: 83%
“…The early evaluation and triage of patients with ST-elevation acute myocardial infarction with telemedicine technologies shortens door to balloon times, reduces infarct size, limits ejection fraction reduction, and shortens length of stay [24]. A dramatic 60% reduction in early and late mortality was observed in large registries on acute myocardial infarction with the use of pre-hospital electrocardiogram supported by telemedicine [25]; pre-hospital triage was an independent predictor for survival at 1 year (hazard ratio: 0.37, 95% confidence interval: 0.18-0.75).…”
Section: Telemedicine For Acute Coronary Syndromementioning
confidence: 99%
“…11) In Japan, a system in which a pre-hospital 12-lead ECG can be sent by fax has been in use until now, but because the information transmission is limited and the usability of the information at the destination hospitals is also limited, this system has never been widely used. In the STAT-MI study, 12,13) it was reported that the time to contact a cardiovascular specialist after the arrival of the EMS team and the time between patient arrival at the hospital and reperfusion were shortened as a result of sending pre-hospital 12-lead ECG data in the form of a PDF file in advance. Moreover, a study in Denmark reported that the door-to-balloon time was shortened by telephotographing a prehospital 12-lead ECG in advance of hospital arrival.…”
Section: Discussionmentioning
confidence: 99%